Does melatonin as an irrigation solution increase the adhesive quality of root canal sealer? (Annals of Medical Research, 2021)
Aim: To evaluate the push-out bond strength of AH-Plus when Melatonin used as an endodontic irrigation.Material and Methods: Ninety extracted human anterior incisors were selected randomly. The teeth were instrumented with R25 Reciproc® files and irrigated according to one of the irrigation protocols included as (n=15): G1: 5.25% NaOCl; G2: 17% EDTA; G3: 0.2% Melatonin; G4: 5.25% NaOCl + 17% EDTA; G5: 5.25% NaOCl + 0.2% Melatonin; G6: 0.2% Melatonin + 17% EDTA. After the root canal obturation procedures, roots were sectioned in coronal, middle and apical of root thirds. Push-out tests were performed Result were analyzed by ANOVA and Tukey tests (P0.05).Results: In the coronal thirds, there were significant differences among the groups. Melatonin+EDTA group showed had greater the bond strength than other groups, except NaOCl+Melatonin. In the middle thirds, NaOCl group showed significantly the lowest bond strength than other groups. In the apical thirds, NaOCl and melatonin groups showed significantly worse (P0.05). Conclusion: The use of Melatonin as a final irrigant significantly increased the push out bond strength of an AH-Plus sealer to root dentin. Further studies are needed to determine appropriate concentration and time used for melatonin.
Keywords: Melatonin; epoxy resin sealer; push-out bond strength.